Computational and experimental demonstrations of one-pot tandem catalysis for electrochemical carbon dioxide reduction to methane - Zhang, Haochen (Nat Commun, 2019)
Electroreduction of carbon dioxide to hydrocarbons and oxygenates on copper involves reduction to a carbon monoxide adsorbate followed by further transformation to hydrocarbons and oxygenates. Simultaneous improvement of these processes over a single reactive site is challenging due to the linear scaling relationship of the binding strength of key intermediates. Herein, we report improved electroreduction of carbon dioxide by exploiting a one-pot tandem catalysis mechanism based on computational and electrochemical investigations. By constructing a well-defined copper-modified silver surface, adsorbed carbon monoxide generated on the silver sites is proposed to migrate to surface copper sites for the subsequent reduction to methane, which is consistent with insights gained from operando attenuated total reflectance surface enhanced infrared absorption spectroscopic investigations. Our results provide a promising approach for designing carbon dioxide electroreduction catalysts to enable one-pot reduction of products beyond carbon monoxide and formate.